2015
DOI: 10.1186/s12993-015-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of caffeic acid on global cerebral ischemia-reperfusion injury in rats

Abstract: Ischemic stroke is a major cause of death and disability all over the world. Ischemic stroke results from a temporary or permanent reduction of cerebral blood flow that leads to functional and structural damage in different brain regions. Despite decades of intense research, the beneficial treatment of stroke remains limited. In light of this, the search for effective means ameliorating cerebral ischemia-reperfusion injury (CIRI) is one of the major problems of experimental medicine and biology. Recently, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 64 publications
6
68
0
Order By: Relevance
“…In an animal model of Parkinson’s disease generated by injection of 6-hydroxydopamine into the rat brain, CAPE prevents dopaminergic neuronal cell loss [49]. Further, Liang et al reported that CA protects cerebral damage against ischemia-reperfusion injury in rats [50]. These reports demonstrate the neuroprotective role of CA and CAPE, highlighting their potentials for treatment of neurodegenerative diseases.…”
Section: Neuroprotection By Coffee Polyphenolsmentioning
confidence: 99%
“…In an animal model of Parkinson’s disease generated by injection of 6-hydroxydopamine into the rat brain, CAPE prevents dopaminergic neuronal cell loss [49]. Further, Liang et al reported that CA protects cerebral damage against ischemia-reperfusion injury in rats [50]. These reports demonstrate the neuroprotective role of CA and CAPE, highlighting their potentials for treatment of neurodegenerative diseases.…”
Section: Neuroprotection By Coffee Polyphenolsmentioning
confidence: 99%
“…In our study, pretreatment of the animals with CA prevented the activation of proinflammatory cytokines, reduced oxidative stress, and protected the kidney function and morphology. CA is a polyphenolic antioxidant that blocks the 5-LOX enzyme, and thereby drop the pro- duction of leukotrienes [9,15]. Moreover, IR activates a sequel of events that leads to upregulation of inflammatory pathways, including TNF-α, cytokines, arachidonic acid, and COX-2 enzyme [16].…”
Section: Discussionmentioning
confidence: 99%
“…CA is also a potent 5-LOX inhibitor [9], as well as a potent antioxidant [10]. In the inflammatory process, CA has been demonstrated to downregulate NF-κB and inhibits tumor necrosis factor alpha (TNF-α), IL-6, IL-1β [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vivo studies mainly focused on neurodegenerative disease (e.g. Alzeimer's), obesity and diabetes, skin cancer, and liver and kidney damage (Table ).…”
Section: Mechanism Of Action Of Hydroxycinnamic Acids: Recent Advancesmentioning
confidence: 99%